2004
DOI: 10.1007/s11745-004-1347-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effect of fish oil supplementation in late pregnancy and early lactation on the n−3 fatty acid content in human breast milk

Abstract: The aim of this research was to investigate the effect of fish oil supplementation, in the third trimester of pregnancy and early lactation period of healthy pregnant Danish women. Forty-four pregnant women were randomly allocated to fish oil supplementation (1.3 g EPA and 0.9 g DHA per day) from week 30 of gestation (FO-group) or to a control regimen (olive oil or no oil; controls). The FO-group was randomly subdivided into women stopping fish oil supplementation at delivery IFO(pregn)], and women continuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 41 publications
3
37
3
6
Order By: Relevance
“…As anticipated, the increases in breast milk n-3 LCPUFA content were greatest in the first months of lactation and were seen without mothers continuing supplementation in the postnatal period. Our findings contrast with those of Boris et al (13) who noted that fish oil supplementation limited to pregnancy was not as effective as supplementation during both pregnancy and lactation and did not significantly increase n-3 LCPUFA content in breast milk compared with a control group. As also anticipated, we have confirmed that maternal n-3 LCPUFA status in late pregnancy is strongly correlated with n-3 LCPUFAs in breast milk for the first 6 wk of lactation.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…As anticipated, the increases in breast milk n-3 LCPUFA content were greatest in the first months of lactation and were seen without mothers continuing supplementation in the postnatal period. Our findings contrast with those of Boris et al (13) who noted that fish oil supplementation limited to pregnancy was not as effective as supplementation during both pregnancy and lactation and did not significantly increase n-3 LCPUFA content in breast milk compared with a control group. As also anticipated, we have confirmed that maternal n-3 LCPUFA status in late pregnancy is strongly correlated with n-3 LCPUFAs in breast milk for the first 6 wk of lactation.…”
contrasting
confidence: 99%
“…previous studies were only short term (13) or used fish oil during lactation [with (14) or without (15) supplementation during pregnancy as well]. To our knowledge, this is the first study to document the effects of high-dose fish oil supplementation during pregnancy on longitudinal changes in breast milk fatty acid composition over the first 6 mo of lactation.…”
mentioning
confidence: 93%
“…In this study, the pregnant mothers had a relatively high educational level. Their RBC-DHA concentrations at baseline (21 weeks pregnant) were close to the values of women in Missouri/USA (gestational weeks [24][25][26][27][28], in Perth/Australia (gestational weeks 20), and twice as high as in an area of Scotland with a very low fish consumption (gestational weeks 15) [14,16,42] . The RBC-EPA values at baseline in our study fit to a moderately low habitual fish consumption of the participants.…”
Section: Discussionsupporting
confidence: 55%
“…[4][5][6][7][8][9][10][11][12][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] No similar systematic reviews were found during the search process. Twenty RCTs were excluded for various reasons.…”
Section: Resultsmentioning
confidence: 99%